The outbreak of COVID-19 and its impact in South Korea’s Tourism: A hope in Domestic Tourism - Kapil Gurung (Politeknik Negeri Bali, 2021)
The recent COVID-19 pandemic has resulted an unprecedented impact on global economy. However, South Korea is effectively controlling the pandemic by implementing different level of social distancing measure. Most of the events are either postponed or cancelled and public places are operating by maintaining social distance and mandatory use of mask. Therefore, the aim of this study is to investigate the future impact on tourism and hospitality industry caused by social distancing due to pandemic. The conceptual methodology was used to discuss on the secondary data from various sources. The finding states that the flight operations were halted, hotel occupancy reduced, and employees forced to take unpaid leave. In addition, the result discussed on the negative impact on tourism and hospitality sector due to pandemic. This paper concludes with few positive signs in domestic tourism sector and suggestion for authority to execute best policy in future for whole tourism industry.